Assessment of the quality of agricultural products and its impact on human endoecology - Kuskova , Valeriia; Korniienko, Iryna; Baranovskyy, Mykhailo (Problems of Environmental Biotechnology, 2021)
The expediency of using biofertilizers and biological products for the protection of agricultural plants during cultivation in comparison with agrochemicals is substantiated. The effectiveness of the use of these biological products in the cultivation of agricultural plants and environmental safety for humans and the environment in general have been proven.